Characterization of Mg-dechelating substance in senescent and pre-senescent Arabidopsis thaliana leaves - Büchert, Agustín M. (2011)
The removal of Mg2+ is an important step in the chlorophyll degradation pathway and extracts from senescent and presenescent Arabidopsis thaliana leaves were analyzed for Mg-dechelatase activity, using chlorophyllin, an artificial derivative of the natural substrate, chlorophyllide. The optimum temperature and pH for this reaction were determined to be at approximately 50 °C and 7.2, respectively. Mg-dechelatase activity was enhanced by addition of EDTA and inhibited by MgCl2, HgCl2 and reduced glutathione, indicating phenomenons such as retroinhibition by reaction products and dependence on the redox state of the mixture. Size exclusion chromatography was performed on Arabidopsis leaf extracts, and Mg-dechelatase activity was found in the fraction corresponding to molecular mass of about 42 kDa, which indicates that the Mg-dechelating compound in Arabidopsis is considerably larger than in other systems. During dark-induced senescence, the activity increased over time until reaching a maximum at day 4, and then decreased. The addition of plant growth regulators indicated that the accumulation of Mg-dechelatase was activated by ethylene and delayed by 6-benzylaminopurine.